Sector public accountability performance measurement: The role of internal factors public sector and accountability as intervening - Jatmiko, Bambang; Haya, Berliana Sofia; Laras, Titi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study examines the influence of leadership style, internal control, organizational culture, organization commitment, organizational performance with public Accountability as an intervening variable on Regional Apparatus Organizations in the Yogyakarta City Government. This study used a sampling method with purposive sampling based on specific criteria. The questionnaire collects the data with 121 respondents from 30 OPDs in the Yogyakarta City Government, which is then further analyzed based on multiple regression and path analysis using SPSS v 22 software application. The results of this study show that leadership style and internal control positively affect the performance of local government organizations. In contrast, the organizational culture and organizational commitment do not positively affect the performance of local government organizations. Thus, public Accountability has a positive effect on the performance of regional government organizations. In addithas leadership style and Internal Control have no positive impact on the performance of local government organizations through public Accountability. In the end, organizational culture and organizational commitment positively affect the performance of local government organizations through public Accountability.